Animal Safekeeping in Situations of Intimate Partner Violence: Experiences of Human Service and Animal Welfare Professionals - Giesbrecht, Crystal J. (Journal of interpersonal violence, 2022)
Although knowledge of the link between intimate partner violence (IPV) and animal maltreatment has increased significantly in recent years, few studies have examined service providers? experiences with IPV and concurrent animal abuse, as well as animal safekeeping in situations of IPV. The present study documented human service and animal welfare service providers? experiences supporting victims/survivors of IPV, who owned pets and livestock, and included service providers in rural and northern communities in Saskatchewan. Online surveys were completed by 128 human service professionals (including domestic violence shelter workers, domestic violence counsellors, victim services workers, police, and legal professionals) and 43 animal welfare professionals (including workers from animal rescues, humane societies, Societies for the Prevention of Cruelty to Animals [SPCAs], and veterinary clinics) (n = 171). Respondents shared information relating to their awareness of the link; their experiences responding in situations of IPV and concurrent animal abuse, including arranging animal safekeeping in situations of IPV; and successes and challenges related to effective service provision. Results include descriptions of intersecting risks to people and animals. Service providers shared ways that they have assisted victims/survivors who own animals, such as through animal safekeeping programs. Both human service and animal welfare professionals expressed the need for pet-friendly domestic violence shelters and pet-friendly long-term housing options. Service providers offered recommendations for improving education and training; improving provision of services of victims/survivors of IPV and their animals, including improving access to Emergency Intervention Orders and establishing funding for animal safekeeping in situations of IPV; and strengthening existing and building new partnerships.